2016
DOI: 10.1038/srep35858
|View full text |Cite
|
Sign up to set email alerts
|

MiR1918 enhances tomato sensitivity to Phytophthora infestans infection

Abstract: Late blight of tomato is caused by the oomycete pathogen Phytophthora infestans. In our previous work, we identified and characterized a miR1918 in P. infestans (pi-miR1918), and showed that its sequence is similar to the sequence of tomato miR1918 (sly-miR1918). In this study, we used Arabidopsis thaliana pre-miR159a as a backbone to synthesize pi-miR1918 via PCR and mutagenesis. The artificial pi-miR1918 was used to investigate the role of miR1918 in tomato-P. infestans interaction. Trangenic tomato plants t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Moreover, Cui and collaborators (2014) evaluated the expression of four micro RNAs using a qRT-PCR-based approach. The first of these studies was able to prove that the miRNA seemed to have a negative effect on the expression of the associated gene [13], and the second was able to corroborate that the miRNA expression levels were as predicted by the bioinformatics analyses [14].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, Cui and collaborators (2014) evaluated the expression of four micro RNAs using a qRT-PCR-based approach. The first of these studies was able to prove that the miRNA seemed to have a negative effect on the expression of the associated gene [13], and the second was able to corroborate that the miRNA expression levels were as predicted by the bioinformatics analyses [14].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, Jia and collaborators (2017) found that the genes with which P. parasitica small ncRNAs overlap are 40% RXLR effector genes, 50% CRN effector genes and some elicitor genes, all well known for their involvement in host-pathogen interactions. These relationships have also been noted for specific types of small ncRNAs such as micro RNAs and transfer RNAs derived small ncRNAs [12,13,14].…”
Section: Introductionmentioning
confidence: 72%
“…A large body of evidence has shown that miRNA-mediated posttranscriptional regulation plays a fundamental role in plant responses to stressful factors, including pathogen infection, salt, drought, heat, cold, nutrient deficiency and metal toxicity [81][82][83][84][85][86]. A great deal of effort has been focused on the identification and functional analysis of plant miRNAs in response to the infection of pathogens, such as viruses [87][88][89], bacteria [16,[90][91][92] and fungi [13,93,94], which have provided valuable information as to the role miRNAs play in plant-pathogen interactions [95,96].…”
Section: Discussionmentioning
confidence: 99%
“…The leaves were harvested at 0, 6, 12, 24, 48, 72, and 96 hr after infection, and the expression levels of miR1916 and target genes were analysed. Necrotic lesion area was measured using the software ImageJ (Luan, Cui, Wang, & Meng, ; Weiberg et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Necrotic lesion area was measured using the software ImageJ (Luan, Cui, Wang, & Meng, 2016;Weiberg et al, 2013). TaKaRa, Dalian, China).…”
Section: Virus-induced Gene Silencing (Vigs)mentioning
confidence: 99%